The phantom Holocaust : Soviet cinema and Jewish catastrophe - Gershenson, Olga, 1969- (New Brunswick, New Jersey : Rutgers University Press, 2013)
Focusing on work by both celebrated and unknown Soviet directors and screenwriters, this is a book about Soviet narrative films dealing with the Holocaust from 1938 to 1991. In addition to studying the completed films, it analyzes the projects that were banned at various stages of production. Archival research and in-depth interviews are used to tell the stories of filmmakers who found authentic ways to represent the Holocaust in the face of official silencing.
Screening the Holocaust in the Soviet Union : Jews without the Holocaust and the Holocaust without the Jews -- Soviet antifascist films of the 1930s : the earliest images of Nazi anti-semitism and concentration camps on world screens -- The first phantom : I will live! (1942) -- How a Soviet novel turned into a Jewish film : the first depiction of the Holocaust on Soviet screens, The unvanquished (1945) -- Thawing the Holocaust on Soviet screen : from Fate of a man (1959) to Ordinary fascism (1965) -- The Holocaust at the Lithuanian film studio : Gott mit uns (1961) -- The Holocaust without the Jews : Steps in the night (1962) and other films -- Kalik versus Goskino : Goodbye, boys! (1964/1966) -- Stalemate (1965) between the filmmaker and the censors -- Kalik's last phantom : King Matt and the old doctor (1966) -- The film that cost a career : Eastern corridor (1966) -- Muslims instead of Musslmans : Sons of the fatherland (1968) -- Commissar (1967/1988) : the end of the thaw -- An alternative track : Jewish soldiers fighting on Soviet screens -- The last phantom, the first film : Our father (1966/1990) -- Perestroika and beyond : old wine in new bottles? -- Conclusions.
Includes bibliographical references (pages 231-267) and index.
Print version record.
English.
JSTOR
Keywords: Holocaust, Jewish (1939-1945), in motion pictures; Jews in motion pictures; Motion pictures -- Soviet Union; Motion picture industry -- Soviet Union; Holocauste, 1939-1945, au cinéma.; Juifs au cinéma.; Cinéma -- URSS; Cinéma -- Industrie -- URSS; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- History & Criticism; Holocaust, Jewish (1939-1945) in motion pictures; Jews in motion pictures; Motion picture industry; Motion pictures; Soviet Union